Implications of the 988 suicide and crisis lifeline among college students experiencing substance use crises - Shaikh, Afroze N. (Journal of addictions & offender counseling, 2024)
Substance use remains a significant concern across college campuses and is associated with adverse mental health outcomes. Low levels of student help-seeking call for innovative forms of support that increase access to care. The new 988 Suicide and Crisis Lifeline has the potential to address this concern through free, 24/7 crisis support. Regression analyses concluded that more frequent substance use significantly predicted lower help-seeking intentions for suicidal thoughts among a sample of 446 college students. Students were also least likely to use the lifeline for substance use concerns as opposed to other mental health concerns. Implications for counselors are provided.